Importance of Big Data in Precision and Personalized Medicine - Naqvi, Muhammad Raza; Arfan Jaffar, Muhammad; Aslam, Muhammad; Shahzad, Syed Khuram; Waseem Iqbal, Muhammad; Farooq, Amjad (2020 International Congress on Human-Computer Interaction, Optimization and Robotic Applications (HORA), 2020)
The rapidly increasing adaptation of Big data technologies in biomedicine, has introduced a revolution in and medical research practice. Trending high-throughput data analysis techniques, have converted the appearance of the biological system to acquire idolization methods for complicated diseases. Majority of the acquired Big-data models govern the materialization of illustrating medicine. This transformation aims at quantification of the period of P4 medicine that will then progressively be more predictive, personalized, pre-emptive, and participatory. It layouts a track to modernize antiseptic methods for the patient's concern center. P4 medicine besides being a scientific face of systems medicine has two highlighted purposes first of which is to evaluate wellness, while the other is, to identify and expose disease. Patients are major operators in the cognizance of P4 medicine as they directly get engaged with a medically familiar network that helps them boost their health. This article will discuss the maturity in big data planning and correlated challenges in biomedicine.